Cognitive Remediation Therapy, Eh! An Exploratory Study at a Canadian Adult Eating Disorders Clinic - Mac Neil, Brad A.; Nadkarni, Pallavi; Leung, Pauline; Stubbs, Laura; O'Brien, Cathy; Singh, Manya; Leduc, Sandra (Canadian Journal of Counselling and Psychotherapy, 2016)
Cognitive remediation therapy (CRT) is a new pretreatment that is not routinely offered as a part of adult eating disorder programming across Canada. This pilot study examined levels of cognitive flexibility, patient satisfaction, life satisfaction, and psychological symptoms in a group of Canadian adults participating in an open ongoing weekly CRT group. Participants were 38 adults who met DSM-5 criteria for an eating disorder. Pre- and postgroup measures of patient satisfaction, psychological flexibility, satisfaction with life, and low mood and anxiety symptoms were completed. Overall, participants were satisfied with the CRT group and experienced significant changes in their levels of psychological flexibility and satisfaction with life postgroup. Preliminary results provide support for further investigation of CRT as a novel and palatable prepsychological group treatment approach for Canadian adults struggling with an eating disorder that can be easily integrated into preexisting evidence-based programming.